The Relationship between Knowledge about Natural Pain Management and the Anxiety of Third Trimester Pregnant Women in Facing Childbirth at the Jatirogo Community Health Center. - Sulastri Sulastri; Retno Dewi Prisusanti (International Journal of Health and Medicine, 2025)
The third trimester of pregnancy is a phase prone to anxiety due to physical and psychological changes and preparation for childbirth. Knowledge of pregnant women plays an important role in shaping mental readiness and reducing anxiety. This study aims to determine the relationship between knowledge levels and anxiety levels of pregnant women in the third trimester. The study used a quantitative correlational approach with 24 respondents selected through accidental sampling technique at Jatirogo Community Health Center, Central Kalimantan. Data were collected using a closed questionnaire and analyzed univariately and bivariately using the Chi-Square test. The results showed that 41.7 % of respondents had good knowledge and 66.7% did not experience anxiety. The Chi-Square test produced a significance value of p = 0.018, indicating a significant relationship between knowledge levels and anxiety of pregnant women. In conclusion, the higher the level of knowledge, the lower the anxiety experienced by pregnant women in the third trimester.